Fear of model misspecification and the robustness premium - Konstantinos Angelopoulos; James R. Malley (Center for Economic Studies and ifo Institute (CESifo), 2010)
Robust decision making implies welfare costs or robustness premia when the approximating model is the true data generating process. To examine the importance of these premia at the aggregate level we employ a simple two-sector dynamic general equilibrium model with human capital and introduce an additional form of precautionary behavior. The latter arises from the robust decision maker's ability to reduce the effects of model misspecification through allocating time and existing human capital to this end. We find that the extent of the robustness premia critically depends on the productivity of time relative to that of human capital. When the relative efficiency of time is low, despite transitory welfare costs, there are gains from following robust policies in the long-run. In contrast, high relative productivity of time implies misallocation costs that remain even in the long-run. Finally, depending on the technology used to reduce model uncertainty, we find that while increasing the fear of model misspecification leads to a net increase in precautionary behavior, investment and output can fall.
Keywords: 330; robustness premium; model misspecification; precautionary behavior; Modell-Spezifikation; Robustes Verfahren; Entscheidung bei Unsicherheit; Wirtschaftspolitik; Kontrolltheorie; Mehr-Sektoren-Modell; Allgemeines Gleichgewicht; Theorie